Principles of database systems - Ullman, Jeffrey D. (Computer Science Press, 1982)
The comprehensive treatment of the theory and general principles relevant to database systems, as well as the many examples, exercises, and bibliographic notes included in each chapter, should make this book useful for database courses and for practising computer scientists.